Role of Live E-Commerce on Consumer Purchase Intentions - Qi, Ling; Masrom, Maslin (Journal of Ecohumanism, 2024)
Purpose: One of the many ways that e-commerce allows shops to use live video to promote products in real time is live streaming. Theoretical structure: Perceived value and trust received are important factors of cognitive response showing interaction with external stimuli in the context of online purchasing study. Approach, methodology, and design: In the end, it influences the customers’ information-seeking behaviour and helps the business create long-term profits by providing information and enabling synchronous information exchange between the online viewer (consumer) and the Internet celebrity. China has set the standard for innovation in internet commerce worldwide, from live broadcasting to cutting-edge purchasing. Results: For live commerce, social engagement, entertainment, and buy intent were found to be positively correlated. However, no relationship between purchase intent and professionalisation or visualisation was found. During live streaming, entertainment has the most influence on viewers’ intention to purchase. Research, Practical, and Social Implications: With the quick advancement of contactless communication, it is projected that the live-streaming e-commerce sector will keep expanding. E-commerce that is live-streamed transcends the traditional notion of solely selling products or services. Originality/value: This study can be used as a standard by future academics and business experts to boost viewers’ propensity to make a purchase while live streaming.